Islamic-based Institutions during Coronavirus Pandemic: A Comparative Case Study of Auckland, New Zealand and Jakarta, Indonesia - Fara Shabira Arrasya; Jesse Hession Grayman (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2021)
This article discusses interventions by Islamic-based institutions during coronavirus pandemic in Auckland, New Zealand and Jakarta, Indonesia. The aim of this article is to compare the interventions implemented by various Islamic-based institutions both in Auckland and in Jakarta. The method consists of literature review, informal interviews, and participant observations. There are three types of Islamic-based institutions: the formal institutions with its hierarchy and leadership, the independent non-governmental communities, and the informal local communities. In Auckland, the interventions were mostly done by the independent non-governmental communities and informal local communities. Kiwi Muslims tended to seek spiritual and material help at the closest Islamic-based institutions. Meanwhile, in Indonesia, the interventions were mostly implemented by formal institutions such as Majelis Ulama Indonesia (Indonesian Council of Ulama) with different kinds of support from large Islamic civil society organizations, such as Nahdalatul Ulama and Muhammadiyah. MUI’s interventions aimed for wide acceptance among all Indonesian Muslims, but fatalistic and deterministic perspectives among many Indonesian Muslims led to low effort in mitigating pandemic and less compliance with MUI and government’s regulations.